Caracterización química y actividad antibacteriana del aceite esencial de Mangifera indica L. de tres regiones de Venezuela - Aparicio zambrano, Rosa; Velasco Carrillo, Judith; Paredes Uzcategui, Rafael; Rojas Fermín, Luis (Revista Colombiana de Química, 2019)
The present work describes the qualitative-quantitative chemical characterization of essential oils (EO) present in the leaves of Mangifera indica L. which were collected in the states of Mérida (M), Barinas (B), and Portuguese (P), in the Bolivarian Republic of Venezuela, using the technique of hydrodistillation, coupled to the trap of Clevenger. Volumes of 0.1 mL (0.0025%), 1.4 mL (0.035%) and 1.0 mL (0.025%) were obtained, respectively. The essential oils were characterized by the method of gas chromatography coupled to mass spectrometry (GC/MS). 30 compounds in the sample collected in M, 24 in B and 14 in P were identified, being the majority in the M: β-selinene (22,56%), α-gurjunene (14,66%) and β-caryophyllene (10 40%); en B: β-caryophyllene (36,32%), α-humulene (22,71%) and α-gurjunene (21,43%); and in P: β-caryophyllene (36.07%), α-gurjunene (22.55%) and α-humulene (21.24%). Due to the low yield, the antibacterial activity was determined in the EO of B and P, by the agar diffusion method with disks, by various international reference bacteria (Staphylococcus aureus ATCC 25923, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922, Klebsiella pneumoniae ATCC 23357, Pseudomonas aureginosa ATCC 27853). Both AE inhibited the development of S.aureus and E. faecalis with a minimum inhibitory concentration of 200 µL/mL and 300 µL/mL, respectively. This is the first comparative study and antibacterial activity of the essential oil obtained from the leaves of M. indica L. in three regions in the Bolivarian Republic of Venezuela.